ChemInform Abstract: Synthesis, Structure, and Spectroscopy of Two Ternary Uranium(IV) Thiophosphates: UP2S9 and UP2S7 Containing P2S92‐ and P2S72‐ Ligands. Issue 35 (8th August 2013) - Babo, Jean‐Marie; Jouffret, Laurent; Lin, Jian; Villa, Eric M.; Albrecht‐Schmitt, Thomas E.
Abstract UP2S9 (I) and UP2S7 (II) are prepared by solid state reaction of 1:1:2:1 mixtures of BaS, U, P2S5, and S or Li2S, U, P2S5, and S, resp.